Observational aspects and analysis of events of severe thunderstorms during April and May 2006 for Assam and adjoining states – A case study on ‘Pilot Storm Project’ - CHAKRABARTI, D; BISWAS, HR; DAS, GK; KORE, PA (MAUSAM, 2008)
A Pilot project on ‘Severe Thunderstorm Observation and Regional Modeling (STORM)’ was undertaken by the Department of Science and Technology during April and May 2006. Regional Meteorological Centre, Guwahati too participated in this project and attempted to monitor each and every severe thunderstorm event. A total of 62 events have been identified on 30 days during 1st April to 25th May. The experiment was restricted upto 25th May in view of onset of monsoon on 27th May. Significant features of all these events are discussed in detail. Satellite imagery and radar echoes of selected events are included to describe the developments of these events. Thermodynamic state of atmosphere along with prevailing synoptic situation associated with the events has been discussed broadly. Results of the study confirm that the ‘Assam valley’ along Brahmaputra river experiences maximum number of events. Lower Assam is more prone to these events as compared to upper and south Assam. High thermodynamic instability, inhomogeneity in horizontal distribution of air temperatures and moisture near ground level and Convective Available Potential Energy (CAPE) value at four stations namely Guwahati, Agartala, Siliguri and Dibrugarh are the key factors in presence of the favourable lower level convergence exhibited by cyclonic circulation over sub-Himalayan West Bengal and adjoining west Assam moving eastwards along Brahmaputra valley with divergence aloft for occurrence of severe thunderstorm over this region. Also In some cases severe thunderstorm outbursts happen in the environment of very low CAPE value also due to proximity of complex terrain feature of this region.